Pendampingan Kegiatan Mencampur Warna untuk Peningkatan Kemampuan Sains Pada Anak Kelompok B di TK Kemala Bhayangkari Bajawa - Meo Maku, Karmelia Rosfinda; Meka, Marsianus; Owa Mere, Veronika (Abdimas Indonesian Journal, 2025)
Science learning in early childhood is an important part in developing critical and exploratory thinking skills. This research aims to determine the effect of assistance with color mixing activities on improving science skills in group B children at an early childhood education institution. The method used is a qualitative approach with observation and interviews as data collection techniques. The results of the research show that through color mixing activities, children are more enthusiastic in learning and are able to understand the basic concepts of mixing primary and secondary colors. Apart from that, they also develop logical thinking skills, observe color changes, and increase curiosity about simple scientific phenomena. Assistance provided by teachers or educators also plays a role in guiding children to be more active and independent in exploring colors. The conclusion of this research is that color mixing activities can be an effective science learning strategy for young children. Therefore, it is recommended for educators to apply simple experiment-based learning methods more often to improve children's learning experiences.